Adaptation and psychometric properties of the Indonesian version of fear of happiness scale - Najib, Asalia; Kumalasari , Asteria Devy (Jurnal Ilmiah Psikologi Terapan, 2023)
A survey of cultural ideas shows that some people have a belief that happiness, especially unnatural levels, should be avoided. This belief is called the Fear of Happiness which is the thought that happiness may have negative consequences. In this study, the researcher intends to adapt the Fear of Happiness Scale measuring instrument developed by Joshanloo (2013). The adaptation process follows the guidelines of the ITC “Guidelines for Translating and Adapting Tests”. Based on trials on 1652 citizens of Indonesia of various ages and cultures, the results of data processing show that this measuring instrument meets the reliability test and test-retest which is processed with Intraclass Correlation Coefficient, as well as evidence of validity, both content validity, factorial and construct validity. Thus, the adaptation is able to measure the image of the fear of happiness in Indonesian society.